2000
DOI: 10.1023/a:1008377101672
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of adjuvant chemotherapy after curative resection for gastric cancer: A meta-analysis of published randomised trials

Abstract: Chemotherapy produces a small survival benefit in patients with curatively resected gastric cancer. However, taking into account the limitations of literature based meta-analyses, adjuvant chemotherapy is still to be considered as an investigational approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
139
1
7

Year Published

2002
2002
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 341 publications
(147 citation statements)
references
References 26 publications
0
139
1
7
Order By: Relevance
“…Postoperative adjuvant chemotherapy for gastric cancer has been thoroughly explored over the past 10 -15 years. Several recent meta-analyses have indicated that, even with pooled data, postoperative adjuvant systemic therapy produces only a modest improvement in survival (Earle and Maroun, 1999;Mari et al, 2000;Janunger et al, 2001). Likewise, adjuvant radiotherapy alone has also failed to demonstrate any survival benefit (Hallissey et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative adjuvant chemotherapy for gastric cancer has been thoroughly explored over the past 10 -15 years. Several recent meta-analyses have indicated that, even with pooled data, postoperative adjuvant systemic therapy produces only a modest improvement in survival (Earle and Maroun, 1999;Mari et al, 2000;Janunger et al, 2001). Likewise, adjuvant radiotherapy alone has also failed to demonstrate any survival benefit (Hallissey et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Although several meta-analyses have suggested that adjuvant chemotherapy provides a survival benefit for gastric cancer [1][2][3][4][5][6][7], efficacy has been established for only a few treatments in large clinical trials. Postoperative radiotherapy with 5-FU plus leucovorin has become a standard adjuvant regimen in the US [8], and the perioperative triplet regimen of epirubicin, cisplatin, and 5-FU is standard in the UK [9].…”
Section: Introductionmentioning
confidence: 99%
“…Until recently there has been relatively little evidence of a survival benefit for established cancer therapies in this disease. However, results from a recent US study have shown a significant survival benefit for the use of adjuvant 5-fluorouracil (5-FU) and radiation in patients following curative resection (MacDonald et al, 2001) and a meta-analysis of the available randomised evidence also supports the use of adjuvant chemotherapy following curative resection (Mari et al, 2000).…”
mentioning
confidence: 99%